The load-carrying capacity of sandwich beams in different collapse mechanisms. (October 2021) - Guo, Lu; Mao, Renwei; Li, Shiqiang; Liu, Zhifang; Lu, Guoxing; Wang, Zhihua
The load-carrying capacity of the symmetrical and asymmetrical sandwich beams, under a quasi-static central load, is investigated in this paper. Three collapse mechanisms such as face yield, core shear and indentation are considered for symmetrical sandwich beams. Core shear mechanism is taken into account for fully clamped asymmetrical sandwich beams. Continuity equations are established by simple 'equal area' method for the postyield behavior of the sandwich beams in face yield and core shear mechanisms at different boundary conditions. In indentation mechanism theoretical model, the effect of the local denting on the large deflection of the sandwich beam is taken into account. Then, finite element simulations are carried out to verify the validity of the proposed analysis, and a good agreement is presented. It is shown that in the core shear mechanism under fully clamped condition, no plateau phase is presented. The effect of the core thickness on the response of the symmetrical beams is discussed in detail. For asymmetry beams in core shear mechanism under fully clamped condition, the effect of the asymmetric factor (strength or thickness) for face-sheets on the load–deflection behavior of the postyield beams can be neglected, if the sum of the strength or thickness of the face sheets is constant.